Al-Ta'āzur bayna Taʿlīm Mahārat al-Qirā'ah ladá Ṭullāb Madrasah Bayt al-Hudá al-Ibtidā'īyah wa-Taʿlīm Qirā'ah wa-Kitābah al-Qur'ān al-Karīm - Achmad Zuhrudin; Erlita Zulfa Nailal Muna (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
One of Baitul Huda Madrasah Ibtidaiyah (elementary school) missions was to instill the habit of Qur'an reading. Thus, daily Qur'an reading activities were implemented in the school. Students who have not been able to read the Qur'an or are older than 12 years old must join the Qur'an reading - writing (BTQ) activity which uses Yanbua method. The purpose of this research is to characterize fifth-grade students' Arabic reading abilities acquired in conjunction with BTQ activities at Baitul Huda elementary school. It was expected that students who followed Yanbua method would improve their Arabic reading abilities, especially reading aloud skill. This research shows that Baitul Huda elementary school employed online and face-to-face Arabic learning methods since the COVID-19 epidemic. In addition, while the fifth graders have an excellent Arabic reading capacity, a few students read Arabic texts with a bit of stutter. Finally, the results of reading skills tests that correlate with BTQ learning indicated that 89.2 percent of students passed and 10.8 percent did not meet the minimal score, indicating that the proportion of BTQ learning positively affects students' Arabic reading ability.